Opportunities and challenges for enhancing preconception health in primary care: qualitative study with women from ethnically diverse communities - Joe Kai; Nadeem Qureshi; Helena Tuomainen; Laura Cross-Bardell; Mandeep Bhoday (BMJ Open)
Objective  There is a growing interest in developing and offering more systematic preconception healthcare. However, it is unclear how this might be regarded by ethnically diverse communities at higher risk of poor maternal and child health outcomes. We sought to explore perceptions about preconception health and care among women from these communities to identify opportunities and challenges for intervention development in primary care.Design Qualitative study using focus groups and semistructured interviews.Setting Ethnically diverse and socially disadvantaged community settings of the UK.Participants 41 women aged 18–45 years, of Pakistani, Indian, Caribbean, African, White and mixed ethnic origin, participating in nine focus groups, half of whom (n=19) had one-to-one follow-up telephone interviews.Results Women had modest or poor awareness of preconception health issues. They perceived these could be addressed in primary care, particularly if raised within a range of clinically ‘relevant’ consultations, such as for contraception, or when opportune for individuals in their social context. However, challenges for engaging women in preconception care more routinely were underlined. These included little prevailing culture of preparing for pregnancy and the realities of their pregnancies often being unplanned; and, for those planning pregnancy, sensitivity and maintaining secrecy when trying to conceive. A preference for female professionals, engaging men, and enhancing access for younger people or women less disposed to general practice, in educational and other settings were highlighted.Conclusions Raising preconception health when this has heightened clinical or social resonance for women may hold promise for initiating more systematic intervention. In primary care this could offer greater potential to directly engage those with low awareness or not considering pregnancy, while enlarging opportunity for others who may be seeking to conceive. Promoting ‘preparation for pregnancy’ more widely might form part of healthcare and education over the life course. Further intervention development research exploring these possibilities, including their feasibility and acceptability is needed.